A walk around Bukhara - Марина Ткачева (Проект Байкал)
The article describes a trip to Uzbekistan and, in particular, to Bukhara – the centre of medieval piety, scholarship, trade. It also features architectural sights of the city. The antiquity of the city is emphasized by numerous legends.